The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1074/jbc.m304750200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Biomass-degrading Enzymes in the Filamentous Fungus Trichoderma reesei

Abstract: The filamentous fungus Trichoderma reesei produces and secretes profuse quantities of enzymes that act synergistically to degrade cellulase and related biomass components. We partially sequenced over 5100 random T. reesei cDNA clones. Among the sequences whose predicted gene products had significant similarity to known proteins, 12 were identified that encode previously unknown enzymes that likely function in biomass degradation. Microarrays were used to query the expression levels of each of the sequences und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
343
3
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 426 publications
(367 citation statements)
references
References 55 publications
14
343
3
7
Order By: Relevance
“…Interestingly, it was also discovered that T. reesei pdi1 is regulated according to the available carbon source, being highly expressed in media where cellulase and hemicellulase genes are strongly induced. A similar result was also obtained with the help of cDNA arrays by Foreman et al (2003), who observed that pdi1 was induced by lactose and sophorose, while 12 other genes involved in folding, glycosylation and vesicle transport were induced only by sophorose.…”
Section: Molecular Characterization Of Secretion Pathway Componentssupporting
confidence: 65%
See 2 more Smart Citations
“…Interestingly, it was also discovered that T. reesei pdi1 is regulated according to the available carbon source, being highly expressed in media where cellulase and hemicellulase genes are strongly induced. A similar result was also obtained with the help of cDNA arrays by Foreman et al (2003), who observed that pdi1 was induced by lactose and sophorose, while 12 other genes involved in folding, glycosylation and vesicle transport were induced only by sophorose.…”
Section: Molecular Characterization Of Secretion Pathway Componentssupporting
confidence: 65%
“…Interestingly, it was also discovered that T. reesei pdi1 is regulated according to the available carbon source, being highly expressed in media where cellulase and hemicellulase genes are strongly induced. A similar result was also obtained with the help of cDNA arrays by Foreman et al (2003), who observed that pdi1 was induced by lactose and sophorose, while 12 other genes involved in folding, glycosylation and vesicle transport were induced only by sophorose.SAR1 is a small GTP-binding protein involved in budding of transport vesicles from the ER membrane (Nakań o & Muramatsu, 1989). The T. reesei sar1 gene was cloned by hybridization with the Aspergillus niger sarA gene (Veldhuisen et al, 1997).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…A portion of the data from two transcriptomics projects identifying T. reesei genes induced by sophorose 27 and cellulose 28 were mapped to the genome. Although not all of the clustered GH genes were coexpressed in the above studies, we found four examples in which adjacent or nearly adjacent genes were coexpressed (Fig.…”
Section: Protein Domains In T Reeseimentioning
confidence: 99%
“…The genomes of filamentous fungi have a large number of predicted glycosyl hydrolases (Ϸ200) with varying numbers of predicted cellulases, from 10 in H. jecorina (11) to 60 in Podospora anserina (20). A comparison between our results and a cDNA expression/Northern analysis of 8 endoglucanases and 7 GH3/␤-glucosidases in H. jecorina (21) showed complete overlap with our profiling data, with the exception of one ortholog of a ␤-glucosidase (cel3e ϭ NCU05577). However, a recent transcriptome/secretome study on the white rot basidiomycete fungus, Phanerochaete chrysosporium (22) showed little overlap.…”
Section: Discussionmentioning
confidence: 87%